(untitled) (CIPEEX, 2025)
Introduction: One of the main global challenges in terms of public health is infection by the Human Immunodeficiency Virus (HIV), the virus causes significant impacts on the immune system and quality of life of infected people. Despite therapeutic advances that include antiretroviral therapy, the deficiency of essential micronutrients such as vitamins and minerals can compromise the immune response and aggravate the progression of the disease, in response to this reality supplementation with nutraceuticals, compounds derived from foods with therapeutic properties, has been studied as an ally in the care of people living with HIV. Objective: This study aims to analyze biotechnological advances with an emphasis on new technologies and the clinical impacts of nutritional supplementation for people living with HIV. Method: The present study is based on an Integrative Literature Review, using published articles in the virtual databases including Pubmed, and the Brazilian Ministry of Health, the choice of this database (PubMed) was of essential importance to the study of micronutrient supplementation and biotechnological advances, because it seeks to identify current scientific evidence that would allow a critical analysis of strategies in health promotion and treatment of people living with HIV. Results: After using inclusion and exclusion criteria, 5 relevant articles were selected that discuss the use of bioinformatics, nanotechnology and controlled-release systems to improve the delivery and efficacy of nutraceuticals, the clinical effects of this supplementation and reinforcing the importance of the nutritional approach as therapeutic support. Conclusion: This study highlighted the potential of biotechnological advances in the delivery of nutraceuticals and how they become fundamental for therapeutic efficacy in the care of people living with HIV, it was also evidenced that the adoption of technologies enhances clinical results, and it is of main importance that public policies incorporate advanced nutritional supplements as part of integrated care.